STUDI PENGELOLAAN OBAT SEBELUM DAN SESUDAH JKN DI PUSKESMAS JETIS KOTA YOGYAKARTA - Alfira Oktaviani; Farida Baroroh (Pharmaciana, 2015)
The effective and efficient drugs management is very crucial in the whole success of public health center management. The government hold a program called National Health Insurance (JKN) in order to achive quality and cost control which is effective and efficient. The research was aimed to know the drugs management at the public health center in Jetis Yogyakarta which includes drug plan, drug demand, drug acceptance, drug storage, drug distribution and the process of drugs recording and reporting. This study used observasional descriptif desaign. Subjects for this study was the implementation of drugs management work instruktion in public health center .TheÂ  technique data collection used triangulation or the combination among stuctured observation result in the form of check list, interview with the human rosources involved of drug management and observation the drug management documentation. The technique analysis used quantative-qualitative descriptive analysis with percentage. The results showed that the drugs management at the public health center Jetis Yogyakarta at the drug plan, was included in both criteria (before JKN 100% and after JKN 100%), the drug demand was included in the criteria quite well (before JKN 63.64% and 63.64% after JKN ), the drug acceptance was included in both criteria (before JKN 100% and after JKN 100%), the drug storage was included in both criteria (before JKN 80.56% and 83.33% after JKN), the drug distribution was included in both criteria (before JKN 76, 92% and after JKN 84.62%), the drug recording and reporting was included in both criteria (prior JKN after JKN 100% and 100%). The general drug management before and after JKN at the public health center Jetis Yogyakarta was applicable standards and good criteria with the percentage of drug management before JKN amounted to 83.91% and after JKN amounted to 86.21%.